2020
DOI: 10.3390/ani10101799
|View full text |Cite
|
Sign up to set email alerts
|

Small Ruminant Production Based on Rangelands to Optimize Animal Nutrition and Health: Building an Interdisciplinary Approach to Evaluate Nutraceutical Plants

Abstract: The plant kingdom can influence the productivity and health of herbivores at different levels. However, demonstrating this process in a scientific manner entails substantial endeavors from different disciplines. In the present review, we will describe the features of a native vegetation system traditionally used by small ruminants and use its particularities to build an interdisciplinary approach to evaluate the nutraceutical properties of plants. Initially, we will establish the context of the low deciduous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 171 publications
0
5
0
3
Order By: Relevance
“…Well-known anthelmintic effects of herbal medicines against the GIN Haemonchus contortus are associated with bioactive compounds, mainly tannins, saponins, and flavonoids, with two possible general mechanisms of action: direct effects on the parasite, or indirect effects by interaction with the host immune system [ 4 ]. The scientific evaluation of plant nutraceuticals against GIN parasites (similar to those developed to assess the efficacy of synthetic drugs against GINs) however, requires a multidisciplinary approach between parasitologists and other scientists [ 5 , 6 ]. Our previous studies found that the effect of medicinal plants on GIN-infected sheep depended on the variety and synergy of polyphenols in medicinal plants and on the combination of bioactive compounds that together had an effect contributing to pharmacological efficacy [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Well-known anthelmintic effects of herbal medicines against the GIN Haemonchus contortus are associated with bioactive compounds, mainly tannins, saponins, and flavonoids, with two possible general mechanisms of action: direct effects on the parasite, or indirect effects by interaction with the host immune system [ 4 ]. The scientific evaluation of plant nutraceuticals against GIN parasites (similar to those developed to assess the efficacy of synthetic drugs against GINs) however, requires a multidisciplinary approach between parasitologists and other scientists [ 5 , 6 ]. Our previous studies found that the effect of medicinal plants on GIN-infected sheep depended on the variety and synergy of polyphenols in medicinal plants and on the combination of bioactive compounds that together had an effect contributing to pharmacological efficacy [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The list was used for the identification and phytochemical description of plants in LUMGS with nutraceutical, prophylactic, and medicinal potential. In addition to such a database, and as suggested by Torres-Fajardo et al (2020), other scientific reports, expert knowledge, New Zealand national plants online database, local knowledge, and public online databases were also considered (refer to Tables 1 and 2).…”
Section: Botanical Survey: Land Cover Database and Surveysmentioning
confidence: 99%
“…Grassland ecosystems are heterogeneous landscapes dominated by herbaceous and shrub vegetation (White et al, 2000). This heterogeneity is not only taxonomic in distinct types of grasses, forbs, shrubs, and trees, but also implicitly distinct in phytochemistry (Torres-Fajardo et al, 2020). The implicit biochemical diversity of taxonomically rich grasslands presents different biochemical structures not only in plant primary metabolites (protein, polysaccharides, minerals, vitamins, and fatty acids) but also in diverse secondary metabolites called plant secondary compounds (PSC), from which benefits for animals, humans, and the environment are multiple (nutritional, medicinal, and prophylactic).…”
Section: Introductionmentioning
confidence: 99%
“…Actualmente se han identificado unas 80,000 plantas que ejercen alguna influencia sobre la salud y la productividad animal (82), por lo tanto, resulta necesario conocer la naturaleza de sus interacciones con los herbívoros y de esta forma poder sugerir su uso como recursos que representen un beneficio nutricional y farmacéutico en los sistemas de producción de ovinos y caprinos (83,84). Estos beneficios podrían estar representados en los denominados alimentos funcionales o recursos nutracéuticos.…”
Section: Experiencias En La Utilización De Terpenos Y Aceites Esenciales Sobre Los Nematodos Gastrointestinales De Ovinos Y Caprinosunclassified